2022
DOI: 10.3390/ijms23042286
|View full text |Cite
|
Sign up to set email alerts
|

An Engineered Nanocomplex with Photodynamic and Photothermal Synergistic Properties for Cancer Treatment

Abstract: Photodynamic therapy (PDT) and photothermal therapy (PTT) are promising therapeutic methods for cancer treatment; however, as single modality therapies, either PDT or PTT is still limited in its success rate. A dual application of both PDT and PTT, in a combined protocol, has gained immense interest. In this study, gold nanoparticles (AuNPs) were conjugated with a PDT agent, meso-tetrahydroxyphenylchlorin (mTHPC) photosensitizer, designed as nanotherapeutic agents that can activate a dual photodynamic/photothe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 71 publications
1
12
0
Order By: Relevance
“…The most studied of doxorubicin mechanism of action today is its ability to integrate into DNA base pairs, causing DNA strand breaks and inhibition of both DNA and RNA synthesis. Doxorubicin inhibits the enzyme topoisomerase II, causing DNA damage and induction of apoptosis [18][19][20][21][22]. It is likely that such effects of doxorubicin are joined by the pro-apoptotic effect of laser irradiation by modulating the metabolism of reactive oxygen species (ROS), in particular through the so-called ROS-induced ROS release, as well as by activating apoptosis regulators [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…The most studied of doxorubicin mechanism of action today is its ability to integrate into DNA base pairs, causing DNA strand breaks and inhibition of both DNA and RNA synthesis. Doxorubicin inhibits the enzyme topoisomerase II, causing DNA damage and induction of apoptosis [18][19][20][21][22]. It is likely that such effects of doxorubicin are joined by the pro-apoptotic effect of laser irradiation by modulating the metabolism of reactive oxygen species (ROS), in particular through the so-called ROS-induced ROS release, as well as by activating apoptosis regulators [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, a group has synthesized a functional complex based on AuNPs covalently linked to meso-tetrahydrobenzyl chloride (mTHPC) drug molecule (AuNP-mTHPC), which enhances the pro-cell death effect of PDT in NB ( Haimov et al, 2018 ). Subsequently, they found that this highly biocompatible and soluble nanotherapeutic agent additionally exhibits a dual PDT/PTT phototoxic effect on NB cells ( Figure 5B ) ( Varon et al, 2022 ).…”
Section: Nanotechnology Enhances Therapeutic Treatment For Neuroblastomamentioning
confidence: 99%
“…(B) AuNP-mTHPC complexes for PDT and PTT dual therapy. Reproduced from ( Varon et al, 2022 ). (C) Photo-magnetic irradiation mediated multimodal therapeutic strategy of NB cells.…”
Section: Nanotechnology Enhances Therapeutic Treatment For Neuroblastomamentioning
confidence: 99%
“…7 In recent years, phototherapy has become an alternative to tumor therapy where the integration of PDT and PTT has demonstrated therapeutic synergism by reciprocally complementing each other and also minimizing the disadvantages of monotherapy. 8…”
Section: Introductionmentioning
confidence: 99%
“…7 In recent years, phototherapy has become an alternative to tumor therapy where the integration of PDT and PTT has demonstrated therapeutic synergism by reciprocally complementing each other and also minimizing the disadvantages of monotherapy. 8 Although multifunctional nanocomplexes with photodynamic and photothermal properties have been developed for TNBC therapy, apart from the complicated synthesis process, inherent limitations including abnormal blood vessels, high concentrations of H 2 O 2 and hypoxia of the TME still need to be overcome. 9,10 Additionally, the PDT causes the restriction of microvascular circulation, which further aggravates hypoxia of the tumors, leading to unsatisfactory performance.…”
Section: Introductionmentioning
confidence: 99%